Dental pulp stem cells as a promising model to study imprinting diseases - Eloïse Giabicani; Aurélie Pham; Céline Sélénou; Marie-Laure Sobrier; Caroline Andrique; Julie Lesieur; Agnès Linglart; Anne Poliard; Catherine Chaussain; Irène Netchine (Nature Publishing Group, 2022)
Abstract Parental imprinting is an epigenetic process leading to monoallelic expression of certain genes depending on their parental origin. Imprinting diseases are characterized by growth and metabolic issues starting from birth to adulthood. They are mainly due to methylation defects in imprinting control region that drive the abnormal expression of imprinted genes. We currently lack relevant animal or cellular models to unravel the pathophysiology of growth failure in these diseases. We aimed to characterize the methylation of imprinting regions in dental pulp stem cells and during their differentiation in osteogenic cells (involved in growth regulation) to assess the interest of this cells in modeling imprinting diseases. We collected dental pulp stem cells from five controls and four patients (three with Silver-Russell syndrome and one with Beckwith-Wiedemann syndrome). Methylation analysis of imprinting control regions involved in these syndromes showed a normal profile in controls and the imprinting defect in patients. These results were maintained in dental pulp stem cells cultured under osteogenic conditions. Furthermore, we confirmed the same pattern in six other loci involved in imprinting diseases in humans. We also confirmed monoallelic expression of H19 (an imprinted gene) in controls and its biallelic expression in one patient. Extensive imprinting control regions methylation analysis shows the strong potential of dental pulp stem cells in modeling imprinting diseases, in which imprinting regions are preserved in culture and during osteogenic differentiation. This will allow to perform in vitro functional and therapeutic tests in cells derived from dental pulp stem cells and generate other cell-types.